Planning of maxillofacial reconstruction with free revascularized fibular autograft: past, present, and future: literary review - O. A. Saprina; I. M. Shpitser (Сибирский онкологический журнал, 2023)
The purpose of the study was to search for data on the evolution of virtual planning of reconstruction with a fibular graft.Material and Methods. A literature search was carried out in Scopus, RSCI databases in the time interval from 1975 to 2021 using the keywords: “computer”, “surgery”, “facial”, “microsurgery”, “fibula”, “implant”, “fibular flap”, “planning”.Results. Various planning techniques with a description of technical features and estimation of advantages and disadvantages as well as methods of minimizing errors and reducing the time spent on the modeling with an improvement in functional and aesthetic outcomes were discussed. Surgical workflows of robot-assisted osteotomies of a fibular graft were described. Complications, difficulties, and the financial aspect of fibula free flap maxillofacial reconstructions were assessed.Conclusion. Virtual planning of microsurgical reconstructions using a fibular graft reduces operating time. The accuracy of graft fixation is increased and diastases between the osteotomy lines as well as between the native jaw and the graft are decreased. Planning allows surgeons to improve symmetry or keep it in the original form, thus affecting the aesthetic aspect and emotional state of the patient. Virtual planning requires certain financial costs, but the wide range of benefits should convince the professionals to use it as often as possible.